The abrupt development of adult-like grid cell firing in the medial entorhinal cortex - Wills, Thomas J.; Barry, Caswell; Cacucci, Francesca (Frontiers in Neural Circuits, 2012)
The neural circuits underlying spatial cognition are created during the development of the brain, and understanding how networks subserving specific cognitive functions are assembled remains a challenge for neuroscience. Here, we characterise the development of grid cells in the medial entorhinal cortex, which, by nature of their regularly spaced firing fields, are thought to provide a distance metric to the hippocampal neural representation of space. Grid cells emerge at the time of weaning in the rat, at around three weeks of age. We investigated whether grid cells in young rats are functionally equivalent to those observed in the adult as soon as they appear, or if instead they follow a gradual developmental trajectory. We find that, from the very youngest ages at which reproducible grid firing is observed (postnatal day 19): grid cells display adult-like firing fields that tessellate to form a coherent map of the local environment; that this map is universal, maintaining its internal structure across different environments; and that grid cells in young rats, as in adults, also encode a representation of direction and speed. To further investigate the developmental processes leading up to the appearance of grid cells, we present data from individual medial entorhinal cortex cells recorded across more than one day, spanning the period before and after the grid firing pattern emerged. We find that different cells show different patterns of development, but that increasing spatial stability may be a common theme.